2007
DOI: 10.1016/j.jnoncrysol.2007.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Smallest (∼10nm) phase-change marks in amorphous and crystalline Ge2Sb2Te5 films

Abstract: Electrical nano-scale crystallization and amorphization in amorphous and crystalline Ge 2 Sb 2 Te 5 films have been studied using scanning probe microscopes. In scanning tunneling microscopes, the phase changes can be induced, not by tunneling currents, but by conducting currents flowing through contacted probes. In an atomic force microscope, metallic cantilevers can produce phase-change marks with minimal sizes of ~10 nm. The crystallization and amorphization processes show different dependences upon thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
(45 reference statements)
0
10
0
2
Order By: Relevance
“…Another parameter, i.e ., the film thickness, is detrimental to a low threshold voltage in the present work. The film thickness ranged between 50 and 60 nm in the present investigation against 20–40 nm for similar study while it was shown that the thicker was the film, the highest was the threshold switching voltage 17, 26.…”
Section: Resultsmentioning
confidence: 99%
“…Another parameter, i.e ., the film thickness, is detrimental to a low threshold voltage in the present work. The film thickness ranged between 50 and 60 nm in the present investigation against 20–40 nm for similar study while it was shown that the thicker was the film, the highest was the threshold switching voltage 17, 26.…”
Section: Resultsmentioning
confidence: 99%
“…Among these attempts is the investigation on scanning probe based storage systems where, similarly to the PCRAM cells, writing of bits by conductive probes involves an electrothermal process in which Joule heating provides the energy required for film crystallization or amorphization. [9][10][11][12][13][14] In this work we report that microstructural and conductivity change of crystalline Ge 2 Sb 2 Te 5 films in the nanoscale range can also be obtained by a mechanical process via nanoscratching. In analogy with laser or electrical writing, the mechanically modified film regions have much lower conductivity than unmodified regions and show microstructural features that are consistent with the amorphous state of the Ge 2 Sb 2 Te 5 alloy.…”
mentioning
confidence: 78%
“…It is also necessary to mention that the writing of an amorphous mark from a crystalline background has been experimentally proven to be difficult due to the required high temperature above the melting point that may oxidize the capping layer [129]. To the best of our knowledge, there is only one research group (Tanaka’s group from Hokkaido University) who have successfully achieved the writing of an amorphous mark that was obtained from a storage stack without the use of a capping layer [115]. Such a structure is not suitable for practical use as the lack of a capping layer would clearly bring several adverse effects such as wear and oxidation into the capping layer.…”
Section: Tertiary Memory Using Pcmsmentioning
confidence: 99%